Sagittal sequence and clinical efficacy of cervical disc replacement and hybrid surgery in the treatment of cervical spondylotic myelopathy: a retrospective study - Zheng, Bin; Xu, Shuai; Lu, Tianliang; Wu, Yonghao; Li, Haoyuan; Guo, Chen; Haiying, Liu (Frontiers in Surgery, 2024)
Background: Hybrid surgery(HS) combines anterior cervical discectomy and fusion (ACDF) with cervical disc replacement(CDR) is gradually being more frequently implemented, but there are few studies reporting the safety and effectiveness of hybrid surgery in three levels cervical spondylotic myelopathy. Methods The clinical and radiographic data of patients with three-segment cervical spondylosis, who underwent CDR，ACDF and HS in our hospital from February 2007 to February 2013 were analyzed. The Visual Analog Scale (VAS), Japanese Orthopedic Association (JOA) and Neck Disability Index (NDI) were used to evaluate the clinical efficacy post surgery. Cervical spine X-rays were conducted to assess ROM,CL,T1S,and relevant outcomes. Results A total of 94 patients were included in the study: 26 in the CDR group, 13 in the HS1 group, 31 in the HS2 group, and 24 in the ACDF group. Most patients in the CDR group were younger. There was no difference in the follow-up duration, blood loss volume or surgery time (P>0.05). Four groups reported improvements in JOA and NDI scores compared to baseline. There was no significant difference in the final JOA, final NDI or recovery rate among the 4 groups. The final ROM was smaller in the ACDF group than in the other 3 groups. There was no difference among the four groups in the final UROM, final LROM or their changes. There was no difference in the final T1S, final SVA or their change among the four groups. All groups showed similar changes in CL and T1S-CL. Conclusions There was no difference in the clinical outcomes of ACDF, CDR, or hybrid surgery. CDR can better preserve the mobility of the cervical spine. Neither CDR nor hybrid surgery was significantly advantageous over ACDF in restoring the sagittal sequence in patients with three-level CSM.